Global mass shootings: comparing the United States against developed and developing countries - Silva, Jason (International journal of comparative and applied criminal justice, 2023)
This study compares mass shootings in the US against developed and developing countries (1998–2019). Findings indicate US mass shootings were more likely to involve workplaces, employment/financial problems, relationship problems, and multiple firearms. Mass shootings in all developed countries (including the US) were more likely than developing countries to involve foreign-born perpetrators, ideological motives, fame-seeking motives, schools, open-spaces, and handguns. Mass shootings in the US account for 73% of all incidents and 62% of all fatalities in developed countries. Mass shootings in developing countries were more likely to involve military and police perpetrators, rifles, and military/police locations. A discussion of findings offers insight for understanding and addressing the global mass shooting problem.